فاعلية الذات وعلاقتها بالسلوك الصحي لدى عينة من المصابين بمرض السكري من المترددين على عيادة سيدي حسين بنغازي (Faculty of Education Scientific Journal, 2024)
The current study aimed to identify the correlation between the self-efficacy variable and the health behavior variable. The researcher relied on the descriptive, correlational approach, and chose the study sample in an intentional manner, amounting to (74) patients attending the Sidi Hussein Clinic in the city of Benghazi. To achieve the objectives of the study, the researcher relied on Collecting data on the self-efficacy scale, prepared by Lajer, translated by Abdul Wahab and Shand (2001), and the health behavior scale, prepared by Sharifa Bin Adqa (2007). The study reached results, the most important of which are:There is a statistically significant correlation between self-efficacy and healthy behavior among a sample of diabetic patients at the Sidi Hussein Clinic in the city of Benghazi.There are statistically significant differences between the average scores of males and the average scores of females on measures of self-efficacy and healthy behavior, in favor of a female sample of diabetic patients.There are no statistically significant differences between the average scores of the study sample of diabetic patients in the variable duration of infection on the self-efficacy and health behavior scales.
Keywords: self-efficacy; healthy behavior; diabetes; diabetics